A groundwater resources study for Santiago City aquifer basin - Navarro, Ephraim N. (2006)
Santiago City Aquifer Basin is located in the province of Isabela, in the north-eastern part of Luzon. Santiago City is becoming highly urbanized and populated which result to rapid increase of water demand for domestic use. Because of strong dependence of the city to groundwater, it is anticipated that accelerated utilization of groundwater may result to over exploitation of the resource if not dealt with properly. This study made evaluations and analyses of groundwater using three-dimensional finite element computer model to assess the availability of groundwater in the study area and come up with recommendations for proper conservation and management of the resource. The recharge comes from rainfall, irrigation water to rice fields and from other surface water like rivers and streams. The model shows that potentiometric surface is relative to the topography of the area, which is high on the upstream side of the rivers and varies in depth towards the low land. Groundwater movement originates from recharge zones then converges to the location of wells. Generally, groundwater moves in the westward direction towards Cagayan River. The present and proposed land use gives about 66,519 m3/day groundwater recharge; however, the potential recharge can arrive up to 88,450 m3/day by applying management and conservation scheme. The magnitude of water demand as a consequence of population growth will have severe impact on groundwater resources in the area. Groundwater versus projected water demand of 85,099 m3/day by2050 indicates that groundwater will be deficient by 18,580 m3/day. This deficiency is expected to increase continuously unless groundwater resources management and conservation strategies are implemented at once.
"October 2006."
Thesis (M.S. in Water Resources)--University of the Philippines Diliman.
Keywords: Water resources development -- Philippines -- Santiago City (Isabela); Groundwater -- Philippines -- Santiago City (Isabela); Aquifers -- Philippines -- Santiago City (Isabela)